2022
DOI: 10.1136/bmjinnov-2021-000887
|View full text |Cite
|
Sign up to set email alerts
|

Youth social innovation during the COVID-19 pandemic in the Philippines: a quantitative and qualitative descriptive analyses from a crowdsourcing open call and online hackathon

Abstract: IntroductionYoung people have played a pivotal role as part of the COVID-19 response, including developing health messages and social innovations. Social innovation in health engages multiple stakeholders in linking social change and health improvement. The study examined the feasibility of youth ideas and innovations to address the impacts of the COVID-19 pandemic using quantitative and qualitative descriptive analyses.MethodsIn partnership with the WHO, academic institutions, youth organisations and civil so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…More than half (24/41) of the publications in this academic discipline were published from 2020–2022 during the COVID-19 pandemic. One emerging variation is the online hackathon event, which became more popular because of the school closures (Franco et al, 2022 ; Happonen et al, 2021 ; Ulitin et al, 2022 ). These studies retrofitted these innovation contests and social gatherings to transform them into remote hackathons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half (24/41) of the publications in this academic discipline were published from 2020–2022 during the COVID-19 pandemic. One emerging variation is the online hackathon event, which became more popular because of the school closures (Franco et al, 2022 ; Happonen et al, 2021 ; Ulitin et al, 2022 ). These studies retrofitted these innovation contests and social gatherings to transform them into remote hackathons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Garcia ( 2022 ) defined hackathons as “ intensive, time-bound events where participants in multidisciplinary teams collaborate and develop innovative solutions to real-world problems ”. The origin of hackathons may be from the technology sector, but they are also now being conducted in education (Affia et al, 2022 ; Pakpour et al, 2022 ; Steglich et al, 2021 ), business (Flores et al, 2020 ; Leemet et al, 2021 ; Valença et al, 2020 ), health (Ulitin et al, 2022 ), and other disciplines (Crook et al, 2022 ; Johnson & Robinson, 2014 ). This expansion recruited a wide range of professionals and talents, bringing domain experts into project teams.…”
Section: Introductionmentioning
confidence: 99%
“…The 12 projects developed by students were taken through the program to develop their innovative ideas through a mentorship program. This study is from an LMIC cognizance of the response rate to participate in hackathon programs as it is observed that in Philippines a crowdsourcing hackathon program for health-care solutions development has attracted over 100 students (Ulitin et al , 2022). To argue the sample size, Warner and Guo(2017) investigated factors that discourage students from participating in hackathons: discomfort, competition and fair on not having experience.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This current study documents various solutions developed by the students from humanitarian logistics and the supply chain in health care to ensure service delivery during a global pandemic. In contrast, a study done in Philippines regarding an open call to participate in an online hackathon on social innovation attracted 113 responses in various domains, including mental health (Ulitin et al , 2022). These are summarized in Table 2.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The study protocol from Li et al examines the effectiveness of a community-engaged social innovation to increase uptake of HIV pre-exposure prophylaxis among sexual minorities in China 31. Crowdsourcing open calls from Malaysia,32 the Philippines,33 Nigeria,34 Ghana35 and the Americas28 identified social innovations using SIHI regional networks. Crowdsourcing has a group of people solve all or part of a problem, then implements or shares solutions with the public 36.…”
mentioning
confidence: 99%